Analysis of Factors Affecting The Quality of Shrimp Paste In Bangkalan District - Choirunnisak Choirunnisak; Fien Zulfikarijah; Nurul Asfiah (Universitas Muhammadiyah Malang, 2022)
This study was conducted to determine the factors considered and the dominant factors considered to affect the quality of shrimp paste. The population of this research is shrimp paste producers in Bangkalan regency with a sample of 96 respondents. Sources of research data using primary data collected through the distribution of questionnaires. The sampling technique used is non-probability sampling with the technique of determining the sample by accidental sampling. The research instrument test uses a validity test, reliability test, and factor analysis as research analysis methods. The results showed that the factors considered affecting the quality of shrimp paste in Kab. Bangkalan, namely production facilities, raw materials, equipment, production processes, maintenance, and the environment.